Perspectives on development of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) - Chao Zhang; Chenliang Zhou; Li Shi; Ge Liu (Taylor & Francis Group, 2020)
The recent outbreak of Coronavirus Disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been characterized by the World Health Organization (WHO) as a controllable global pandemic. The spike (S) glycoprotein mediates binding to the angiotensin-converting enzyme 2 (ACE2) receptor for virus entry and also services as the target of virus-neutralizing antibodies, making it an attractive and leading viral antigen for vaccine development. No vaccine against any human coronavirus is available to date. In learning from the experience of developing Middle East respiratory syndrome coronavirus (MERS-CoV) and SARS-CoV vaccine candidates in preclinical and clinical trials, the most promising strategies for SARS-CoV-2 vaccines should employ viral-vector platforms, properly adjuvanted recombinant protein or DNA/mRNA encoding an engineered sequence of trimeric S protein in pre-fusion conformation.